Modelling of the adsorption of chlorinated phenols on polyethylene and polyethylene terephthalate microplastic - Lončarski Maja; Tubić Aleksandra; Kragulj-Isakovski Marijana; Jović Branislav; Apostolović Tamara; Nikić Jasmina; Agbaba Jasmina (Journal of the Serbian Chemical Society, 2020)
The role of microplastics (MPs) on the fate and transport of various pollutants in water matrices is of major concern, but it is still relatively under investigated. In order to consider the conditions in real aquatic environments, the changes to polyethylene (PE) structure during the fabrication of microplastic particles for specific uses should not be neglected. Thus, this work considers isolated PE from two types of personal care products, which are possible sources of microplastic contamination in aquatic environments. The adsorption affinity of these PE microplastics towards ionisable compounds was compared with those of standards of PE and polyethylene terephthalate (PET), using chlorinated phenols (4-chlorophenol, 2,4-dichlorophenol, 2,4,6-trichlorophenol and pentachlorophenol) as adsorbates. The pseudo-second order kinetic model described well the sorption process for all chlorinated phenols on all four types of MPs (R2 range: 0.900–0.998). The kinetic study showed that sorption rates are mainly controlled by hydrophobic interactions and molecule size. Adsorption isotherms were best described by the Freundlich model for all MPs. The obtained results indicate that MPs could serve for the transport of chlorinated phenols through ambient waters. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. III43005]